Central nervous system inflammatory demyelinating disorders of childhood - Kamate, Mahesh (Medknow Publications, 2010)
BACKGROUND AND OBJECTIVES: Childhood Central Nervous System (CNS) inflammatory demyelinating disorders (CIDD) are being diagnosed more commonly now. There is ambiguity in the use of different terms in relation to CIDD. Recently, consensus definitions have been proposed so that there is uniformity in studies across the world. The prevalence of these disorders and the spectrum varies from place to place. This study was undertaken to study the clinico-radiological profile and outcome of children with CIDD using the recent consensus definition. STUDY DESIGN: Prospective descriptive study. MATERIALS AND METHODS: All patients admitted in pediatric ward and pediatric intensive care with neurological symptoms and signs suggestive of CNS inflammatory demyelinating disorders from July 2007–August 2008 were enrolled. The details of clinical presentation, neuroimaging findings, laboratory results, treatment, and outcome were noted and analyzed. RESULTS: Fifteen patients (11 with acute disseminated encephalomyelitis and 4 with clinically isolated syndrome) were diagnosed with CIDD. Clinical presentation was quite varied. Eight patients recovered completely; 4 cases were left with sequelae and 3 patients expired. There were no cases of multiple sclerosis or neuromyelitis optica. CONCLUSIONS: CNS inflammatory demyelinating disorders are common illnesses in developing countries because of recurrent infections. Even the spectrum of CIDD is different. Neuroimaging in the form of magnetic resonance imaging is essential for diagnosis.